Fast-tracking for total knee replacement reduces use of institutional care without compromising quality. (4th March 2018) - Pamilo, Konsta J; Torkki, Paulus; Peltola, Mikko; Pesola, Maija; Remes, Ville; Paloneva, Juha
Abstract : Background and purpose — Fast-tracking shortens the length of the primary treatment period (length of stay, LOS) after total knee replacement (TKR). We evaluated the influence of the fast-track concept on the length of uninterrupted institutional care (LUIC) and other outcomes after TKR. Patients and methods — 4, 256 TKRs performed in 4 hospitals between 2009–2010 and 2012–2013 were identified from the Finnish Hospital Discharge Register and the Finnish Arthroplasty Register. Hospitals were classified as fast track (Hospital A) and non-fast track (Hospitals B, C and D). We analyzed length of uninterrupted institutional care (LUIC), LOS, discharge destination, readmission, revision, manipulation under anesthesia (MUA) and mortality rate in each hospital. We compared these outcomes for TKRs performed in Hospital A before and after fast-track implementation and we also compared Hospital A outcomes with the corresponding outcomes for the other 3 hospitals. Results — After fast-track implementation, median LOS in Hospital A fell from 5 to 3 days (p < 0.001) and (median) LUIC from 7 to 3 (p < 0.001) days. These reductions in LOS and LUIC were accompanied by an increase in the discharge rate to home (p = 0.01). Fast-tracking in Hospital A led to no increase in 14- and 42-day readmissions, MUA, revision or mortality compared with the rates before fast-tracking, or with those in the other hospitals. Of the 4 hospitals, LOS and LUIC were most reduced in Hospital A. Interpretation — A fast-track protocol reduces LUIC and LOS after TKR without increasing readmission, complication or revision rates.